Imagination, geniuses and thought collectives - Mścisławski, Łukasz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
In his book Wojciech Sady attempts to reconstruct the structure of the fundamental transformations that can be described as the relativistic and quantum revolution. Referring to rich historical material and Ludwik Fleck’s reflections on the development of scientific knowledge, the author tries to explain how it is possible that “scientists began to think differently than they had been taught.” Sady’s work, although not devoid of somewhat weaker points, is a brave and thought-provoking attempt to propose his own explanation of the mechanisms of the aforementioned transformations.